Edith Stein – sv. Terezija Benedikta od Križa o duhovnosti ženske - Primc, Liza (Bogoslovni vestnik, 2024)
Throughout her life, the German philosopher and theologian Edith Stein - St Teresa Benedicta of the Cross (1891–1942) was surrounded by images of women which shaped her thinking about women. After her conversion, she expressed her thoughts on women in writings published posthumously in Die Frau. In her study Spirituality of the Christian Woman, Stein questions the spiritual nature of a woman and her vocation in the World, while at the same time offering fundamentals for a comprehensive balance for every woman.
Keywords: Duhovnost kristjanke; duhovnost ženske; image of woman; podoba ženske; Spirituality of a Christian woman; spirituality of woman; Stein, Edith